رؤية مستقبلية مقترحة لتطوير تخصص الصحة النفسية - الشافعي، نهلة فرج علي (رابطة التربويين العرب, 2024)
تهدف هذه الدراسة إلى صياغة رؤية مستقبلية لتطوير تخصص الصحة النفسية في الجامعات المصرية من خلال المرور بعدة مراحل تضمنت المرحلة الأولى منطلقات الرؤية المستقبلية المقترحة لتطوير تخصص الصحة النفسية والتي تمثلت في رؤية مصر ۲۰۳۰، والتصنيفات العالمية للجامعات ومعاييرها، وخطة عمل منظمة الصحة العالمية ٢٠١٣-٢٠٣٠م والاستراتيجية الوطنية للصحة ۲۰۲۳-۲۰۳۰م، والمستجدات المحلية والعالمية المرتبطة بمجال الصحة النفسية، يليها مرحلة وصف وتحليل واقع تخصص الصحة النفسية ومؤسساته في مصر باستخدام استراتيجية SWOT من خلال بيان نقاط القوة والضعف والفرص والتهديدات؛ وبناء على ذلك تم صياغة التصور المستقبلي لتطوير التخصص رؤية ورسالة وأهدافا، وصياغة الخطة التشغيلية بتحديد الخطوات الإجرائية ووضع بعض الآليات المقترحة لتنفيذ خطة تطوير تخصص الصحة النفسية والجهات المسئولة عن التنفيذ. This study aims to formulate a future vision for developing the mental health specialty in Egyptian universities by going through several stages. The first stage included the starting points for the proposed future vision for developing the mental health specialty, which were: Egypt Vision 2030, international university classifications and their standards, and the World Health Organization’s 2013 action plan. 2030 AD, the National Health Strategy 2023-2030 AD, and local and global developments related to the field of mental health, Followed by the stage of describing and analyzing the reality of the mental health specialty and its institutions in Egypt using the SWOT strategy by stating the strengths, weaknesses, opportunities and threats; Accordingly, the future vision for developing the specialty, a vision, mission, and goals, was formulated, and the operational plan was formulated by specifying the procedural steps and setting some proposed mechanisms for implementing the mental health specialty development plan and the entities responsible for implementation.
Keywords: تطوير التعليم -- الصحة النفسية -- التنمية المستدامة -- مصر